Concurrent intrathoracic and extrathoracic congenital lung malformations - Ritah Chumdermpadetsuk; Claire Gerall; Steven Rothenberg; Susie Chen; Vincent Duron (Elsevier, 2021)
Congenital lung malformations (CLM) are most commonly determined to be congenital pulmonary airway malformations (CPAM) followed by bronchopulmonary sequestration (BPS) and hybrid CPAM/BPS lesions. Although prenatal diagnosis of intrathoracic CLMs is common, extrathoracic CLMs are rare with histopathologically confirmed diagnosis of simultaneous intrathoracic and extrathoracic CLMs not yet reported in literature. In the setting of both an intrathoracic and extrathoracic congenital lung lesion, currently no data exists addressing the timing as well as order in which the lesions should be resected. We present the case of a patient prenatally diagnosed with a left intralobar as well as a left infradiaphragmatic CLM, both confirmed on pathology as hybrid CPAM/BPS lesions. The lesions were resected in two separate minimally invasive operations, with resection of the intrathoracic lesion occurring at 4 months of age and the extrathoracic lesion following at 9 months. In the absence of symptoms, we suggest resection of intrathoracic lesions prior to extrathoracic lesions due to the increased risk of pulmonary infection.